The Influence of Injection Ovaprim by Different Dosage to Ovulation and Hatching of Tambakan (Helostoma temmincki C.V) - Yurisman ' (Berkala Perikanan Terubuk, 2009)
This research was conducted 5 to 20 February 2008 at Fish BreedingLaboratory Fisheries and Marine Science Faculty of Riau University. It was aimto know the influence of hormone ovaprim to ovulation and fertilized includepercentages of hatcing and survival rate of larva ”tambakan” (Helostomatemmincki C.V). It the research experiment method was applied with fourtreatments and tree replications. The treatment injection by fisiologis solution0,65 %, injection by ovaprim 0,3 ml/kg, 0,5 ml/kg and 0,7 ml/kg weigh of fish.The result showed that the injection by ovaprim indicated different parameters infew treatment. The best result was got from 0,7 ml/kg doze with latent time 5hours, total of eggs ovulated 30.072 eggs, diameter 0,38 mm and 17 % eggripeness. But this doze did not give effect for the percentage of fertilization,percentage of hatching and survival rate of larva tambakan (Helostoma temmincki C.V).